CONCEPTUALIZING THE LIVEABLE AFRICAN CITY - Taibat Lawanson; Taofiki Salau; Omoayena Yadua (Journal of Construction Project Management and Innovation)
This paper attempts to conceptualize the liveable African City using indices of liveability as advanced by Africans. The concepts of City Liveability and the City as a living system are used as the theoretical underpinnings to the study. A purposive online questionnaire survey of 453 Africans, living both in Africa and the Diaspora was conducted to elicit their perspectives on what they consider the most important indices for a Liveable African City. The data was disaggregated on locational basis. This was done to determine whether ones location i.e. living at home or in the Diaspora contributes significantly to one’s opinion on the identified issues. Issues investigated include governance, safety and security, culture and global identity, environmental indices and infrastructure. Furthermore, the inherent contradictions between western and African concepts of liveability were examined. The study revealed that 67% of all respondents consider governance to be the most important determinant of city liveability. Cultural heritage and city image were considered the least important indices of urban liveability. In determining the choice of where to live, 82.2% of respondents consider quality of life, while few differentials existed based on location, safety and security, particularly violent crime and the threat of terror were considered extremely important by respondents living in the Diaspora. The study concludes by recommending the application of broad based urban management strategies combined with good urban governance mechanisms to improve city liveability across the continent.